Working properties of some selected refractory clay deposits in South Western Nigeria (2008)
"Working properties of some clay deposits in Ekiti State, Nigeria were investigated with a view to determine their suitability for use as refractory bricks. The samples were collected from three different commercial pottery clay centers in Ekiti State; they are Ara, Awo and Isan. Two varieties were collected from both Ara and Isan, which are named Ara 1, Ara 2, and Isan 1, Isan 2 respectively while only one type was collected from Awo. The clay samples were crushed, pulverized, sieved and their chemical compositions were determined. The clay samples were treated separately as well as blended together in different proportions and moulded into bricks. The bricks were dried and fired to 1050°C. Tests for refractoriness, thermal shock resistance, shrinkage, thermal expansion; bulk density, porosity, and compressive strength were carried out on each batch specimen. The results showed that Ara 2 and Ara 1, 2 combined in equal proportions displayed the highest thermo chemical stability. They also possess comparatively high cold crushing strength, and high thermal shock resistance, but definitely not the highest. The apparent porosity of all the batch specimens was found to be high as well as the bulk densities, while the shrinkage of all the specimens were low. It was concluded that 100% Ara 2, and a blend of Ara 1 and 2 in equal proportions, are most suitable for production of crucibles, and furnace lining for non ferrous metals processing, such as Aluminium, Lead and Bronze. "